PENERAPAN CERVICAL STABILIZATION MELALUI ACTIVE EXERCISE MENINGKATKAN KEMAMPUAN FUNGSIONAL DAN PRODUKTIVITAS KERJA PENENUN ENDEK DI INDUSTRI TENUN IKAT DENPASAR - Fauziah, Enny; Sutjana, I Dewa Putu; Handari Adiputra, Luh Made Indah Sri; Tirtayasa, Ketut; Sutajaya, I Made; Suardana, Putu Gede Ery (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 4 No 1 (2018): Volume 4 No 1 Juni 2018, 2018)
Characteristics of weaver was done by sitting on a chair in front of the loom. Sitting position for ± 8 working hours, monotonous movement, shoulders slightly raised, causing workers to balance body position. Work posture cause a static contraction to the shoulder and neck muscles. This study aims to show that the application of cervical stabilization through active exercise every 2 hours after work increase functional ability seen from decreasing musculoskeletal complaints, fatigue, increasing neck disability index and productivity among workers in weaving industry.        This experimental study has been done, with treatment by subject design. Period 1 subject is not treated ie weaving as usual. Period 2 subjects were treated with the application of cervical stabilization through active exercise every 2 hours after work. Between the two stages, washing out period and adaptation. Musculoskeletal complaints were measured by Nordic Body Map questionnaire, work fatigue with 30 item of rating scale, neck functional ability measured with neck disability index and productivity based on output and input ratio.        Analysis of the collected data is started with the descriptive analysis and the normality data tested using Shapiro-Wilk. Further, the data that has normal distribution are analyzed using t-paired and the data that has not a normal distribution are analyzed using Wilcoxon test . This study show that the application of cervical stabilization through active exercise increase functional ability seen from decreasing of musculoskeletal complaint 17.05%, fatigue 19.78%, increasing of neck disability index 15.13% and productivity 66.67%.        It can be concluded that the application of cervical stabilization through active exercise increase functional ability seen from musculoskeletal complaints, work fatigue, neck disability index and work productivity. So it is suggested to apply to weavers in the weaving industry, to increase the functional ability of workers.